A consideration on the impact of HSR on the aviation sector in view of the recent Japanese case. (2016) - Hayashi, Taizo
Shinkansen, the Japanese high speed rail (HSR) service, started its operation in the northern part of mainland Honshu and Kyushu districts in late 2010 and early 2011. Consequently, the modal shares of rail versus air for travels to and from these areas have shifted substantially. This paper aims to identify factors to be considered in analysing the modal choice of travelling public where modal competition between railway and aviation sector exists. Although the introduction of HSR services has led to the overall increase in the modal share of railway and decrease in the modal share of air transport, situations would differ from area to area, reflecting the local circumstances that are specific to each area. The study finds that HSR has been successful in capturing a considerable portion of travel demand in the short-to-medium distance markets, and the introduction of LCC operation helps to prevent and mitigate the decrease in the modal share of air transport.